Processos de imitação-criação como constituidores da práxis pedagógica: uma intervenção didático-formativa com o formador de professores - Sousa, Walêska Dayse Dias de (2016)
The research deals with the constitution of the pedagogical praxis of a teacher trainer, understood as objectification of theoretical and practical unity in the teaching field. It was achieved by means of a didactic-training intervention. The research problem: as a teacher trainer in a continuous training process is a pedagogical praxis, outlined to the overall objective: investigate the establishment of the pedagogical praxis of teacher trainer in a continuous formation process. The specific objectives were: 1) outline principles and foundations theoretical-methodological course of intervention research on appropriate teaching assumptions of historical-cultural theory; 2) systematic principles of constitution of the pedagogical praxis of a teacher trainer and 3) synthesize foundations of continued training of teacher trainers in view of the historical-cultural theory, to collaborate with design of institutional policies for continuing training of university teachers. The research was developed at the Federal University of Triângulo Mineiro University - UFTM, with teachers who work in their degree courses. It was developed in three stages: diagnosis, didactic-formative intervention and analysis of data. In the diagnostic step attended five teacher educators of degrees in: history, geography, physics, chemistry and letters. At this stage were used identification questionnaires, interviews, classroom observation and document analysis. In the next stage, with participation of a trainer, it was held educational-training intervention understood as the collective research-training process that is involved intervening in teaching with the development of interdependent and simultaneous actions trainings, planning and implementation of educational activities and study, classroom observation and evaluation from the perspective of dialectical unity in order to contribute to the integral development of teachers and students. The intervention were also held interviews and document analysis. The last stage of the research was the analysis of the data. In the diagnosis of education, among other analyzes, three references were found of the trainer's training-action: memorized references, empirical and praxis. It was the analysis of the references of the trainer's training-action that guided referrals ways of teaching-training intervention. As a result, it was concluded that the teacher educator is their pedagogical praxis in the dialectical units theoretical and practical appropriation of concepts and imitation-creation. Were the two principles analyzed in the research. It was also systematized some essential elements of the formation of the teacher educator: the needs of trainers are decisive in the choice of concepts that will be appropriate; the organization of the training process should take place hand in hand with planning and development classes; the theory need to be experienced in training so that appropriation/objectification of education come true, and also, participants must be strengthened as a collective studies, since we have not learned by linearity but connections. It is hoped that the research will create opportunities to deepen the debate on the continuing education of teacher educators and contribute to scientific production in the area.